Religion and Occultism: Contestation of Islam and Local Culture in Malay Society - Hermansyah Hermansyah (IAIN Pekalongan, 2020)
In Malay Archipelago, Malay is associated with Islam. Malay people who migrate to Malay Archipelago centuries ago have embraced Islam as their faith. Islam is spread across Malay Archipelago peacefully. Those who spread Islam in this region didn’t destroy the principles of local communities. Some local traditions were even used to spread Islam. Therefore, Islam in the faith and practice of Malay people still contains local elements, including magic—known by Malay people as ilmu. Ilmu is closely related with belief, ideas, and lifestyles of the practitioners. As a tradition, Ilmu strengthens local beliefs and practices. The arrival of Islam has changed the dialectic ilmu of Malay people. In the dialectic process between local tradition and Islamic elements, there is contestation. This paper describes the relation of a form of contestation between local elements and Islam in the Ilmu of Malay people. The dynamics of the contestation are ongoing. The competition is sometimes won by local elements, so its strengthened. But, sometimes local elements are defeated and fully replaced by Islamic elements. However, some Islamic and local elements are found to exist side-by-side.